PERCEIVED SOURCES OF STRESS AMONG UNDERGRADUATE DENTAL STUDENTS IN INDIA – A CROSS SECTIONAL SURVEY - Nagesh, Lakshminarayan; GV, Usha (International Journal of Research -GRANTHAALAYAH, 2022)
Objective: To investigate the perceived sources of stress, the role of parents, socio-cultural background and the learning environment on the stress levels of the students studying dentistry in Bapuji Dental College, Davanagere, India. Methods: In this cross sectional survey 320 dental students were invited to participate, and 284 responded, resulting in a response rate of 88%. A self administered 42 close ended Dental Environment Stress (DES) questionnaire was used to assess various sources of stress. Results: The sample consisted of the subjects in the age range of 17-28 years, 59.5% of the students joined dentistry as their self choice followed by 9.5% due to parental choice and 31% as they had no other option. Analysis of Variance (ANOVA) revealed perceived sources of stress between classes and across all classes: final year students ranked high (3.32±0.87) due to examinations and grades. Difficulty in learning precision manual skills for doing clinical and laboratory work resulted in highest stress among the first years (2.45±0.83). Working on patients with dirty mouth resulted high amount of stress in final year students (2.84±0.95). Conclusion: The increased amount of stress among dental students highlights the importance of periodic interaction between the students, college faculty and educational psychologists to maximize performance of the students and minimize stress.